Structures of Accountability in the Parish and Diocese: Lessons Learned in North America and Possibilities for Reform - Glendinning, Chad J. (Studia canonica, 2022)
The Code of Canon Law identifies a number of participative structures at both the diocesan and parish level whose purpose is to assist diocesan bishops and parish priests in their duties. Despite this, recent events have shown that structures and procedures designed to ensure accountability were ineffectual or lacking altogether. After a brief consideration of the concept of accountability, this study will proceed to examine these various participative structures. The limitations of these structures and possibilities for reform will be identified, to assist the Church along its 'path of synodality'.